2017
DOI: 10.1111/cea.13049
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the field of allergy in 2016 through the eyes of Clinical and Experimental Allergy

Abstract: In this article, we described the development in the field of allergy as described by Clinical and Experimental Allergy in 2016. Experimental models of allergic disease, basic mechanisms, clinical mechanisms, allergens, asthma and rhinitis, and clinical allergy are all covered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 130 publications
(225 reference statements)
0
2
0
Order By: Relevance
“…Our results agree with the fact that grass pollen is one of the most frequent reasons for plant-related allergenic reactions worldwide. It is thought that at least 40% of patients with respiratory allergies worldwide are sensitized to grass pollen allergens [29], which comprise 9,000 different grass species (Poaceae) [30]. Timo et al demonstrated that grass was the most frequent cause of pollen allergy in Europe and the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with the fact that grass pollen is one of the most frequent reasons for plant-related allergenic reactions worldwide. It is thought that at least 40% of patients with respiratory allergies worldwide are sensitized to grass pollen allergens [29], which comprise 9,000 different grass species (Poaceae) [30]. Timo et al demonstrated that grass was the most frequent cause of pollen allergy in Europe and the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with the notion that grass pollen is one of the most frequent reasons for plant-related allergenic reactions worldwide. It is thought that at least 40% of patients with respiratory allergies worldwide are sensitized to grass pollen allergens, 32 which comprise 9,000 different grass species (Poaceae). 33 Hugg et al, 2017 demonstrated that grass was the most frequent cause of pollen allergy in Europe and the USA.…”
Section: Discussionmentioning
confidence: 99%